Self-Compassion: Association with Psychological Symptoms and Usage in Psychotherapy - Burcu Korkmaz (Psikiyatride Güncel Yaklaşımlar, 2018)
Self-compassion is defined by Neff as approaching to the self without judgment, criticism or punishment, sharing the stressful experiences with other people without isolation and holding the painful emotions and thoughts in mindful awareness without over identification. The studies showed that self-compassion has positive relationship with psychological well-being; has negative relationships with depression, anxiety, eating disorders, trauma and other psychological problems. Also, the findings from psychotherapy studies that try to strength self-compassion attracted a great deal of attention. The main aims of this article were reviewing the self-compassion concept toward the literature, summarizing the empirical findings in the context of self-compassion and discussing the usage of self-compassion in psychotherapy.